High-Resolution 3D Whole-Heart Coronary MRA: A Study on the Combination of Data Acquisition in Multiple Breath-Holds and 1D Residual Respiratory Motion Compensation - Forman, Christoph; Piccini, Davide; Grimm, Robert; Hutter, Jana; Hornegger, Joachim; Zenge, Michael O. (Magnetic Resonance Materials in Physics Biology and Medicine, 2014)
Object: To study a scan protocol for coronary magnetic resonance angiography based on multiple breath-holds featuring 1D motion compensation and to compare the resulting image quality to a navigator-gated free-breathing acquisition. Image reconstruction was performed using L1 regularized iterative SENSE. Materials and methods: The effects of respiratory motion on the Cartesian sampling scheme were minimized by performing data acquisition in multiple breath-holds. During the scan, repetitive readouts through a k-space center were used to detect and correct the respiratory displacement of the heart by exploiting the self-navigation principle in image reconstruction. In vivo experiments were performed in nine healthy volunteers and the resulting image quality was compared to a navigator-gated reference in terms of vessel length and sharpness. Results: Acquisition in breath-hold is an effective method to reduce the scan time by more than 30 % compared to the navigator-gated reference. Although an equivalent mean image quality with respect to the reference was achieved with the proposed method, the 1D motion compensation did not work equally well in all cases. Conclusion: In general, the image quality scaled with the robustness of the motion compensation. Nevertheless, the featured setup provides a positive basis for future extension with more advanced motion compensation methods. © 2014 ESMRMB.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD5.highre
Keywords: Compressed sensing; Coronary magnetic resonance angiography; Multiple breath-holds; Respiratory motion compensation

Novel Projection-Based Unsupervised Respiratory Motion Feedback for Free-Breathing Whole-Heart Coronary MR Imaging - Forman, Christoph; Piccini, Davide; Hornegger, Joachim; Zenge, Michael O. (Proceedings of the 21st Annual Meeting of ISMRM, 2013)

Reduction of Respiratory Motion Artifacts for Free-Breathing Whole-Heart Coronary MRA by Weighted Iterative Reconstruction - Forman, Christoph; Piccini, Davide; Grimm, Robert; Hutter, Jana; Hornegger, Joachim; Zenge, Michael O. (Magnetic Resonance in Medicine, 2014)
Purpose: To combine weighted iterative reconstruction with self-navigated free-breathing coronary magnetic resonance angiography for retrospective reduction of respiratory motion artifacts. Methods: One-dimensional self-navigation was improved for robust respiratory motion detection and the consistency of the acquired data was estimated on the detected motion. Based on the data consistency, the data fidelity term of iterative reconstruction was weighted to reduce the effects of respiratory motion. In vivo experiments were performed in 14 healthy volunteers and the resulting image quality of the proposed method was compared to a navigator-gated reference in terms of acquisition time, vessel length, and sharpness. Result: Although the sampling pattern of the proposed method contained 60% more samples with respect to the reference, the scan efficiency was improved from 39.5±10.1% to 55.1±9.1%. The improved self-navigation showed a high correlation to the standard navigator signal and the described weighting efficiently reduced respiratory motion artifacts. Overall, the average image quality of the proposed method was comparable to the navigator-gated reference. Conclusion: Self-navigated coronary magnetic resonance angiography was successfully combined with weighted iterative reconstruction to reduce the total acquisition time and efficiently suppress respiratory motion artifacts. The simplicity of the experimental setup and the promising image quality are encouraging toward future clinical evaluation. © 2014 Wiley Periodicals, Inc.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD5.reduct
Keywords: Compressed sensing; Coronary magnetic resonance angiography; Motion suppression; Weighted iterative reconstruction

Respiratory Self-Navigation for Whole-Heart Coronary Magnetic Resonance Imaging - Piccini, Davide (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)
As the average life span of the world population increases, cardiovascular diseases firmly establish themselves as the most frequent cause of death in many of the developed countries. Coronary artery disease (CAD) is responsible for more than half of these cases and there is, hence, a strong need for a non-invasive and radiation-free test that could be reliably adopted for its assessment in clinical routine. Although coronary magnetic resonance imaging (MRI) has always been regarded with high expectations, it is still not considered for clinical assessment of CAD. This is mainly due to several limitations of current coronary MRI examinations. The complex anatomy of the coronary arteries requires extensive scout-scanning to precisely plan the actual data acquisition. The current speed limitations of the MRI scanners and the contribution of cardiac and respiratory motion do not allow the high resolution acquisitions to be performed within the fraction of a single heartbeat. Consequently, data acquisition must be split into multiple heartbeats and usually performed during free-breathing. At the same time, gating with respect to a consistent respiratory position is applied using an interleaved navigated scan which monitors the position of the subject's diaphragm. Major improvements in standard navigator-gated free-breathing coronary MRI have been achieved in recent years, but a number of important intrinsic limitations, such as the prolonged and unknown acquisition times, the non-linearity of the motion compensation, and the complexity of the examination setup have so far hindered the clinical usage of this technique. In contrast, a technique known as self-navigation, which performs motion detection and correction solely based on imaging data of the heart, promises a priori knowledge of the duration of the acquisition with improved accuracy of the motion compensation and requires minimal expertise for the planning of the examination. In this work, a novel acquisition and motion correction strategy for free-breathing self-navigated whole-heart coronary MRA was introduced, analyzed and implemented to be entirely integrated in a clinical MR scanner. The proposed acquisition method consists of a novel interleaved 3D radial trajectory, mathematically constructed on the basis of a spiral phyllotaxis pattern, which intrinsically minimizes the eddy currents artifacts of the balanced steady state free-precessing acquisition, while ensuring a complete and uniform coverage of k-space. The self-navigated respiratory motion detection is performed on imaging readouts oriented along the superior-inferior axes and is based on a method for the isolation and automatic segmentation of the bright signal of the blood pool. Motion detection of the segmented blood pool is then performed using a cross-correlation technique. This fully automated respiratory selfnavigated method offers an easy and robust solution for coronary MR imaging that can also be integrated into a regular clinical routine examination. The technique was tested in volunteers, compared to the standard navigator-gating approach, and, for the first time to the author's knowledge, allowed self-navigation to be positively applied to a large patient study in an advanced clinical setting.<br
UnivIS-Import:2016-07-26:Pub.2014.tech.IMMD.IMMD5.respir_3
Keywords: coronary MRI; motion compensation; self-navigation